Using binary fuzzy goal programming and linear programming to resolve airport logistics center expansion plan problems - Tu, Chang-Shu; Chang, Ching-Ter (Applied soft computing, 2016)
[Display omitted] •DAHP, ZOGP and BMGP methods for airport logistic center expansion plans are proposed of both qualitative and quantitative criteria.•This study considers operating costs, plan budget and contractor assignment issues in the problem.•Airport ground handling services (AGHS) companies have enhanced to provide convenient services for passengers and to broaden the AGHS market. In recent years, the number of direct flights between Taiwan and mainland China has grown rapidly, as charter flights have been turned into regular flights. This important issue has prompted airport ground handling service (AGHS) companies in Taiwan to enhance convenient services for passengers and to invest in airport logistics center expansion plans (ALCEP) to broaden the AGHS market. Due to their budgetary restrictions, AGHS companies need to outsource many of their services to contractors to implement these plans. This study proposes an ALCEP solution procedure to guide AGHS companies in adjusting their priority goals and selecting the best contractor according to their needs. This proposed procedure successfully solves the ALCEP problem and facilitates the assignment of contractors by considering both qualitative and quantitative methods.